The profile of compromise skills in collaborative learning environments in elementary schools - Daryanto, Joko; Karsono, Karsono; Wiraman, Mahdum; Rukayah, Rukayah; Budiharto, Tri; Yahya, Ayyas (Jurnal JPSD (Jurnal Pendidikan Sekolah Dasar), 2024)
Collaboration is one of the essential "4C" skills required to foster learning that responds to students’ adaptation needs in a 21st-century environment. An important aspect of collaboration that can be examined in group-based, problem-solving learning is productive teamwork. This study explores the productive teamwork aspect of collaboration skills among sixth-grade students at SD Negeri Setono, utilizing Greenstein’s framework, particularly in the context of problem-based learning. This research adopts a descriptive qualitative approach. The study participants include both students and teachers of the sixth grade at SD Negeri Setono Surakarta. Data collection methods comprised observations, interviews, questionnaires, and documentation studies. To ensure data validity, technique and source triangulation were applied. The collected data were then analyzed through the interactive data analysis model of Miles and Huberman. Findings from this study reveal that students are able to work productively in group-structured, problem-based learning settings. This is evidenced by the manifestation of all productive teamwork indicators within the learning activities. The productivity demonstrated by students is further supported by other facets of collaboration skills